Optimization study on palm fat base (HAMIN®) and purified water proportion in diphenhydramine hydrochloride cream formulation - Winarti, Lina; Gazzali, Amirah Mohd; Arafika, Whendy Waliya; Ameliana, Lidya; Ulfa, Evi Umayah; Nurahmanto, Dwi; Paramayuda, Farukh (Universitas Ahmad Dahlan, 2025)
HAMIN® is a self-emulsifying base composed of a mixture of hydrogenated palm kernel oil and hydrogenated palm kernel stearin. This formulation not only enhances the aesthetic quality of products but also simplifies the manufacturing process, as it eliminates the need for additional emulsifying agents to form a stable cream. Due to these properties, HAMIN® is considered highly suitable for the development of both pharmaceutical and cosmetic formulations. Despite its potential applications, no prior research has investigated the optimal ratio of HAMIN® palm fat base to distilled water distilled waterrequired to achieve desirable physical characteristics and drug release properties in cream formulations. Therefore, this study aims to determine the optimum composition of HAMIN® palm fat base and distilled water for the formulation of diphenhydramine hydrochloride cream. The optimization process was conducted using the simplex lattice design (SLD) method, a statistical approach commonly employed to evaluate and optimize multicomponent formulations. The experimental results demonstrated that increasing the concentration of HAMIN® palm fat base had a dominant effect on enhancing the pH, viscosity, adhesion, and stability of the cream. Conversely, a higher concentration of distilled water significantly improved spreadability, extrudability, and drug release flux. These findings indicate that the selection of base composition plays a crucial role in determining the overall performance of the cream formulation. The optimal formulation, as determined through SLD analysis, consisted of 41.667% HAMIN® palm fat base and 48.333% distilled water, achieving a desirability index of 0.649. This composition represents the most balanced formulation in terms of physical stability and drug release, making it a promising candidate for further pharmaceutical and cosmetic applications.